Satisfacción laboral del profesional de la salud para la mejora del desempeño en el hospital Dr. Aníbal González Álava – 2018 - Hidalgo Bravo, Sully Pierina (2019)
The main objective of this research was to evaluate the impact on the performance of the health professionals of the Dr. Aníbal González Álava Hospital in 2018, in order to improve the quality of the services. Which began with field research and bibliography in order to acquire primary and secondary information that supports research work in order to know the current situation of the organization? It should also be noted that techniques were applied: the interview that allowed contact with the Director of the Hospital where information was obtained that helped to know the reality or the current state of the work environment of the health professionals, the survey that was applied to the 32 health professionals. The instrument NTP 394 was applied that served as a guide to identify which are these psychosocial factors that affect job satisfaction, the Herzberg scale allowed to determine both intrinsic and extrinsic factors and take the valuation scale with their respective questions to give it more support and truthfulness It should be noted that job satisfaction at a general level in professionals shows that 50% are satisfied, 19% very satisfied and with the same percentage moderately satisfied, while a 6% neither satisfied nor dissatisfied, 3% are moderately satisfactory and finally with 3% are the unsatisfactory, so it is concluded that the institution needs an improvement plan that is on track to mitigate or eliminate those nonconformities that the health professional has.